Learning Fiqh Joyfully: Developing Snakes and Ladders Game to Enhance Students' Understanding of Thaharah - Ainun Munzidah; Miftakhul Ilmi Suwignya Putra; Lilik Maftuhatin; Anjuma Paradisa; Amjad Ali Jokhio (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study was driven by the lack of students’ interest and understanding in learning Fiqh, particularly in the topic of thaharah, despite the fact that it is a fundamental concept for every Muslim. A contributing factor to this issue is thought to be the limited use of innovative and engaging learning media. This research aims to develop a learning media (snakes and ladders) to enhance student learning outcomes in Fiqh, focusing on thaharah, at MTs Babussalam Kalibening Jombang. The study employs a Research and Development (R&D) approach, adapting the ten-step model by Borg & Gall. These steps include data collection, planning, initial product development, individual trials, product revision, small group trials, second revision, and large group trials. The resulting product is a large-scale snakes and ladders game integrated with a quiz related to thaharah content. Validation results show that it received an average score of 4.2 from media experts (valid), 4.25 from subject matter experts (very valid), and 4.3 from practitioners/teachers (very valid). Trial implementations (individual, small group, and large group) revealed high levels of student engagement. This is also supported by the result of post test that shows improvement in learning outcomes. In conclusion, the snakes and ladders media is feasible and effective for improving students’ learning outputs in Fiqh subject.